Working in the school as a complex organization. Theoretical perspectives, models, professionalism for the Secondary School - Lucia Balduzzi; Giovanna Del Gobbo; Loredana Perla (Firenze University Press, 2018)
Lavorare nell'organizzazione complessa scuola. Prospettive teoriche, modelli, professionalità per la Secondaria di I e II grado